MOTIVATION FOR STUDENTS LEARNING ENGLISH ON DIGITAL MEDIA DURING THE COVID-19 PANDEMIC AT EIGHT GRADE OF MTs MUHAMMADIYAH 3 MASARAN - Virda Laily Rahmawati; Sri Handayani (English Education Department Slamet Riyadi University Surakarta, 2022)
The objectives of this research were followed: 1) Implementation digital media forstudents’ eight grade to learn English at MTs Muhammadiyah 3 Masaran and 2) motivatethe students’ eight grade to learn English using digital media at MTs Muhammadiyah 3Masaran. The research used descriptive qualitative which conducted in OctoberNovember 2021, The subject of the research was the students of especially 8A with 22students at MTs Muhammadiyah 3 Masaran in 2020/2021 academic year. The researcherused observation, interview and questionnaie with teacher and students’ to collect thedata. The researcher used data triangulation to analyze data of observation, interview andquestionnaire the researcher used the table questionnaire and share via whatsapp. Theresults of the research on student learning motivation consisted of intrinsic and extrinsicfactors by knowing the character of students to increased motivation and interested inlearning, giving a positive response to learning English used digital media during theCovid-19 pandemic, could foster students' independent learning attitudes. Teachers andschools could provide good motivation to students in the right way, such as prepared anddesigning teaching materials according to the needs, competencies of students, providingfacilities and infrastructure. So that students are interested in the learning process and canmotivate themselves to be active in learning English, especially by using digital media.Keywords: Motivation, Learning English, Digital Media